PS1 - 218 Characterization of Ganglioglioma as a Neurodevelopmental Disorder: A Cast of Arrested Development?. (18th October 2016) - Jiang, Q.; Zagozewski, J.; Nozza, P.; Wilson, B.; Van Landeghem, F.; Eisenstat, D.D
Abstract : Gangliogliomas (GG) are low grade neuroepithelial tumours of the central nervous system (CNS) comprised of neoplastic glial and neuronal cells. There are no animal models or cell lines to study. Microarray data of a panel of low grade gliomas including GG revealed overexpression of the DLX2 homeobox gene required for tangential interneuronal migration and differentiation in the embryonic forebrain. We hypothesized that DLX2 regulates neural versus glial cell fate decisions in CNS progenitors and that GG are arrested in development. METHODS: DLX2 expression was examined along with glial fibrillary acidic protein (GFAP; glial marker) and synaptophysin and/or NeuN (neuronal markers) expression in a cohort of GG tumours using immunohistochemistry and dual immunofluorescence labelling of formalin fixed paraffin embedded (FFPE) tissue sections. BRAF mutational status was also assessed. RESULTS: In our discovery cohort (Genoa), 10/30 samples (33%) expressed DLX2. In our validation cohort (Edmonton), 22/36 (61%) expressed nuclear DLX2 and 12/22 DLX2+cases had BRAF mutations (55%; 11 V600E, 1 V600G). 12/18 cases with BRAF mutations were DLX2+(67%). One heavily pre-treated child with progressive cervicomedullary GG has had a very good partial response to BRAF inhibitor therapy. All 22 DLX2+tumours co-expressed GFAP (100%) and 21/22 (95%) also expressed synaptophysin or NeuN. CONCLUSIONS: Our results support GG as neurodevelopmental tumours arising from bipotential CNS progenitors that are arrested at the neural-glial cell fate "decision" point. Biological or differentiation-based treatments could be considered+/- BRAF inhibitors for those GG with/without the V600E mutation, respectively.